2000
DOI: 10.4049/jimmunol.165.8.4667
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Roles of Integrins During Leukocyte Development and Traffic: Insights from the Analysis of Mice Chimeric for α5, αv, and α4 Integrins

Abstract: Integrins 4 α , and v α , 5 α

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 34 publications
(32 reference statements)
2
64
0
Order By: Relevance
“…These findings are quite remarkable given the relatively minor reduction in IEL number observed in a E -deficient mice [6] and illuminate a hitherto under-appreciated redundancy in the integrin system for maintaining lymphocytes within the intestinal mucosa. Studies of chimeric a 5 -, a V -, or a 4 -null/recombinaseactivating gene (RAG)-2-deficient mice have demonstrated that these a subunits are not essential for maintaining normal IEL numbers in the small intestine [21]. However, a 1 -deficient mice are reported to have a 50% reduction in IEL number [13].…”
Section: Discussionmentioning
confidence: 99%
“…These findings are quite remarkable given the relatively minor reduction in IEL number observed in a E -deficient mice [6] and illuminate a hitherto under-appreciated redundancy in the integrin system for maintaining lymphocytes within the intestinal mucosa. Studies of chimeric a 5 -, a V -, or a 4 -null/recombinaseactivating gene (RAG)-2-deficient mice have demonstrated that these a subunits are not essential for maintaining normal IEL numbers in the small intestine [21]. However, a 1 -deficient mice are reported to have a 50% reduction in IEL number [13].…”
Section: Discussionmentioning
confidence: 99%
“…Studies using mice chimeric for either the α4, α5, or αv subunit, which are the β1-associated α subunits on leucocyte progenitors, indicate that none of these integrins is required for colonization of the fetal haematopoietic organs but they do implicate α4 in the multilineage development of haematopoietic cells and in lymphocyte homing to lymph nodes and Peyer's patches [106,107]. Defective homing to Peyer's patches is also observed in mice deficient in β7, another β subunit with which α4 can combine to form the α4β7 integrin that recognizes MadCAM, an endothelial receptor expressed in the gut [108].…”
Section: Haematopoietic Cellsmentioning
confidence: 99%
“…[73][74][75][76] However, studies with chimeric mice with homozygous deletions of integrin ␣ chains have not settled the role of individual integrin ␣ chains in stem cell homing, and it is possible that multiple receptors are involved. 14,[77][78] In vitro studies have shown a migration promoting activity for both laminin-10/11 and laminin-8 in tumor cell lines 22,79 and mouse integrin ␤2-deficient granulocytes. 55 We therefore here analyzed the effect of laminin-8 and laminin-10/11 on transmigration of CD34 ϩ cells stimulated with the chemokine SDF-1␣.…”
Section: Discussionmentioning
confidence: 99%